Canadian Annual Review of Politics and Public Affairs 1961 - Saywell, John T., 1929-2011 (Book collections on Project MUSE., 1962)
Here is an indispensable reference book for those concerned directly or indirectly with Canadian public affairs. The Canadian Annual Review is not only a concise and convenient record of the year, but a responsible appraisal of important developments related in perspective. It has been expressly prepared for this purpose by a special panel of recognized experts, writing under the direction of a leading Canadian historian and political commentator. As succeeding volumes appear, the Canadian Annual Review will grow in value; in the years ahead, a complete series of volumes will provide a clear historical perspective of the present and the immediate past. For rapid review of any important topic, for convenient checking of the course of a piece of legislation, for quick determination of a death date, or for information on the circumstances of a major government appointment or retirement - there are hundreds of uses which will make the Canadian Annual Review a regular reference habit. Its place will regularly be on the desk rather than the shelf. The superb index is not only a guide to the first edition of this important reference work; it is the only index to the history of the time. And in addition to being concise and completely authoritative, the Canadian Annual Review is readable. The articles it contains can be read consecutively for the interest they possess and the instruction they offer, or they can be spot-read with ease to locate particular information.